Pengaruh Inovas Produk dan Marketing Tools Terhadap Keunggulan Bersaing Produk di Toko Lapak Sepatu Medan - Shinta Dewi; Mutiah Khaira Sihotang (Jurnal Ekonomi dan Keuangan Syariah, 2022)
The purpose of this study was to determine the effect of product innovation and marketing tools on the competitive advantage of fashion products at the Medan Shoe Store. This type of research uses quantitative research. The population in this study were the consumers of the Medan Shoe Store on Jl. Halat No. 122a Medan and samples used were 80 minimum samples using the Slovin formula, but to strengthen the results of the study, the researchers rounded off the results of the minimum sample calculations by distributing questionnaires to 100 respondents. Data collection techniques used in this study are questionnaires and documentation. The analytical model used in this study is a regression analysis model, with a partial test method with Ttest and simultaneous test with Ftest. The partial T test results show that Product Innovation and Marketing Tools partially have a significant effect on Competitive Advantage. And the results of the F test simultaneously (simultaneously) have a significant effect on Competitive Advantage. So it can be concluded that there is an effect of Product Innovation and Marketing Tools on competitive advantage.